Low-dose ethanol intake prevents high-fat diet-induced adverse cardiovascular events in mice. Issue 4 (9th April 2020) - Nie, Junhui; Ngokana, Linel Darrel; Kou, Jiayuan; Zhao, Yuchen; Tu, Jiajie; Ji, Heng; Tan, Peizhu; Zhao, Tingting; Cao, Yuwei; Wu, Zhaojing; Wang, Qi; Ren, Shuangfeng; et al.
Abstract : This study aimed to clarify whether low-dose ethanol intake could prevent high-fat diet-induced adverse effects on cardiomyocytes in mice. Abstract : A high-fat diet is recognized as an important factor in the development of cardiovascular diseases including cardiomyopathy. Besides high-fat diets, large quantities of ethanol also induce cardiomyopathy in both animals and humans. Emerging evidence suggests that low ethanol intake may have a protective effect on the cardiovascular system. This study aimed to clarify whether low-dose ethanol intake could prevent high-fat diet-induced adverse effects on cardiomyocytes in mice. After 6–8 weeks of feeding, the heart weight significantly decreased in ethanol + HFD mice compared to HFD mice. In addition, cardiac triglycerides and lipid droplets also decreased, but no statistically significant difference in cholesterol level was found between the two groups. Expression of the fatty acid transporters Cd36, Slc27a1 and Got2 was downregulated in the ethanol + HFD group. According to echocardiography, the mass and volume of the left ventricle were reduced, and the ejection fraction (EF) and fractional shortening (FS) were increased in mice fed with alcohol. Low doses of ethanol reduced the cardiomyocytes' cross-sectional area and the expression of the hypertrophic markers ANP and BNP. Moreover, Col1a1, the main collagen type expressed in the heart, was also reduced by low-dose ethanol consumption. Also, the expression of Rgs5, a crucial component of the signaling pathway involved in cardiac remodeling and heart failure, was upregulated in response to ethanol intake. The data suggest that low ethanol intake prevents adverse effects induced by a high-fat diet, such as lipid accumulation, cardiac dysfunction, hypertrophy and fibrosis. Furthermore, low ethanol intake upregulates Rgs5, which suggests it plays a role in cardiac remodeling and heart failure.